Perbedaan Struktur Mikro, Kekerasan, dan Ketangguhan Baja HQ 705 Bila Diquench dan Ditemper pada Media Es, Air dan Oli - Darmawi Bayin; M Amin Indra Putra (Universitas Sriwijaya, 2009)
This research is aim to analyze the effect of quench at difference medium on the hardness and the impact of HQ 705 steel which is as similar as AISI 4340 with 0.38 – 0.43% C; 1.82% Ni; 0.5% - 0.8% Cr and 0,25% Mo. HQ 705 steel is heated to austenite temperature of 8500 C and hold as long as 15 minutes and cooled at the difference mediums, which is water, ice and oil. After that, the steels being tempered at temperature of 5500 C and hold as long as 30 minutes, and then again cooled. Finally, the specimens are tested to find hardness, toughness and microstructure. Through this research, we find the increase of hardness, from 33.4 HRC at no treatment to 56 HRC at cooling in water, 40.3 HRC at cooling in oil.